2020
DOI: 10.1002/cam4.3367
|View full text |Cite
|
Sign up to set email alerts
|

Identification of small molecule drugs and development of a novel autophagy‐related prognostic signature for kidney renal clear cell carcinoma

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…( 23 ) AUC = 0.729; Xing et al. ( 24 ) AUC = 0.724] and found that our signature had higher prediction reliability and sensitivity than other published biomarkers ( Figure 4D ). Subsequently, the univariate ( Figure 4E ) and multivariate Cox regression analysis ( Figure 4F ) were performed and confirmed that risk score, age, grade were independent prognostic factors (p < 0.01).…”
Section: Resultsmentioning
confidence: 64%
“…( 23 ) AUC = 0.729; Xing et al. ( 24 ) AUC = 0.724] and found that our signature had higher prediction reliability and sensitivity than other published biomarkers ( Figure 4D ). Subsequently, the univariate ( Figure 4E ) and multivariate Cox regression analysis ( Figure 4F ) were performed and confirmed that risk score, age, grade were independent prognostic factors (p < 0.01).…”
Section: Resultsmentioning
confidence: 64%
“…We compared the prognostic‐related ARlncRNAs signature with published predictive models in KIRC patients. The ROC curves showed that the present signature (AUC = 0.809) had higher predictive reliability and sensitivity than other published biomarkers (Chen et al 16 autophagy‐related (AR) mRNA signature, AUC = 0.723; Liu, et al 17 lncRNA signature, AUC = 0.723; Sun, et al 18 immune‐related lncRNA, AUC = 0.709; Yin, et al 19 lncRNA signature, AUC = 0.684; Sun, et al 20 m6A‐related signature, AUC = 0.698; Wan, et al 21 AR‐mRNA signature, AUC = 0.743;Xing, et al 22 AR‐mRNA signature, AUC = 0.723; Yang, et al 23 AR‐mRNA signature, AUC = 0.741; Zhang, et al 24 lncRNA signature, AUC = 0.781; Figure 8).…”
Section: Resultsmentioning
confidence: 99%
“…Nomogram, as a predictive tool, has been widely applied to help clinical decision-making [46][47][48]. In our article, we created a nomogram to intuitively predict OS probabilities in ccRCC, by means of NOP2 and eight clinical parameters (gender, age, grade, stage, T stage, race, N stage, M stage).…”
Section: Discussionmentioning
confidence: 99%